Endometrial Cancers in Mutation Carriers From Hereditary Breast Ovarian Cancer Syndrome Kindreds: Report From the Creighton University Hereditary Cancer Registry With Review of the Implications. Issue 4 (May 2015) - Casey, Murray Joseph; Bewtra, Chhanda; Lynch, Henry T.; Snyder, Carrie L.; Stacey, Mark
Abstract : Objective: The aim of this study was to categorize and report endometrial cancers in mutation carriers from hereditary breast ovarian cancer families. Methods: Our Hereditary Cancer Registry was searched for gynecologic and peritoneal cancers linked to mutations in BRCA1 or BRCA2 . Invasive cancers were registered in 101 mutation carriers with complete pathology reports. Efforts were made to secure diagnostic surgical pathology tissues for review. All records and available diagnostic slides were meticulously studied, and primary cancers were classified. Findings: Eight malignancies were classified as primary endometrial cancers. Five of these were low- or intermediate-grade endometrioid carcinomas, and 3 were pure serous carcinomas or contained serous carcinoma elements mixed with high-grade endometrioid carcinoma. Breast cancers were diagnosed in 5 patients before and in 1 patient after endometrial carcinoma. Three endometrioid carcinomas were preceded by estrogen treatment, 2 for many years and the other for only 2 months, and 2 of the patients with serous carcinoma had been treated with tamoxifen. Conclusions: The finding that 8 of gynecologic and peritoneal cancers in 101 mutation carriers were endometrial cancers with a smaller proportion of endometrioid carcinomas than reported in general populations is added to the current controversial literature on endometrial cancer, particularly regarding serous carcinomas, in hereditary breast ovarian cancer syndrome. Well-designed prospective programs for standardized surgical and pathologic handling, processing, and reporting are essential for working out the pathogenesis, true risks, and best management of this disease in carriers of deleterious BRCA1 and BRCA2 germline mutations.